Practical Principles & Practical Judgment - O'neill, Onora (The Hastings Center report, 2001)
Those who deny that general principles are important for moral deliberation have mostly misunderstood how principles work. Principles do not give us algorithms for living. They identify broad requirements we must live up to, but they do not actually tell us what to do. We are left instead to craft responses that honor our general commitments using the materials of the case at hand.